1980
DOI: 10.1104/pp.65.1.88
|View full text |Cite
|
Sign up to set email alerts
|

Potassium Chloride as Stomatal Osmoticum in Allium cepa L., a Species Devoid of Starch in Guard Cells

Abstract: K+ and Clr contents of guard cells and of ordinary epidermal cells were determined in epidermal samples of Alium cepa L. by electron probe microanalysis; malate contents of the same samples were determined by enzymic oxidation. KCI was, in general, the major osmoticum in guard cells, irrespective of whether stomata had opened on leaves or in epidermal strips floating on solutions. lation ofP-enolpyruvate (14). P-enolpyruvate is very likely derived from starch (4). In guard cells of Viciafaba, the balance betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
29
0
1

Year Published

1982
1982
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(33 citation statements)
references
References 16 publications
3
29
0
1
Order By: Relevance
“…This starch-sugar hypothesis (Lloyd, 1908) was the accepted theory until the 1960s, when it was replaced by the K + -malate theory (Imamura, 1943;Fischer, 1968;Raschke, 1975) correlating stomatal opening with K + uptake, along with the counter ions malate 22 and/or Cl 2 (Allaway, 1973;Schnabl and Raschke, 1980;Outlaw, 1983). As outlined above, this became accepted as the main osmoregulatory pathway and often is still considered the exclusive mechanism for regulating stomatal aperture.…”
Section: The Suc Paradox Role For Suc In Guard Cell Osmoregulationmentioning
confidence: 99%
See 1 more Smart Citation
“…This starch-sugar hypothesis (Lloyd, 1908) was the accepted theory until the 1960s, when it was replaced by the K + -malate theory (Imamura, 1943;Fischer, 1968;Raschke, 1975) correlating stomatal opening with K + uptake, along with the counter ions malate 22 and/or Cl 2 (Allaway, 1973;Schnabl and Raschke, 1980;Outlaw, 1983). As outlined above, this became accepted as the main osmoregulatory pathway and often is still considered the exclusive mechanism for regulating stomatal aperture.…”
Section: The Suc Paradox Role For Suc In Guard Cell Osmoregulationmentioning
confidence: 99%
“…It seems, however, that the contribution of malate as a counter ion for K + depends on the availability of Cl 2 and can range between 50% and 90% of total cellular osmolytes (Raschke and Schnabl, 1978). In the extreme case of onion (Allium cepa), which lacks starch in guard cells, malate accumulation is not observed and Cl 2 is used as the exclusive counter ion (Schnabl and Raschke, 1980;Amodeo et al, 1996).…”
mentioning
confidence: 99%
“…Studies with epidermal peels have demonstrated strong correlations between stomatal opening and malate accumulation in guard cells (Allaway, 1973;Pearson, 1973;van Kirk and Raschke, 1978) and with the use of a PEPC inhibitor (DCDP) it has also been shown that stomatal opening is restricted when PEPC activity is reduced in epidermal strips (Parvathi and Raghavendra, 1997). In epidermal strips, the importance of malate as a counter ion to K 1 is influenced by the availability of chloride (van Kirk and Raschke, 1978;Schnabl and Raschke, 1980;Willmer and Fricker, 1996). The low g s and epidermal PEPC content in the pp mutants show that maximum stomatal opening is dependent on PEPC activity and presumably malate in the guard cells in vivo.…”
mentioning
confidence: 99%
“…Chlorophylls are very important for plants because, they allow plants to perform photosynthesis and stabilize proteins that bind and protect them from degradation. Reaction centers contain chlorophyll a, while light harvesting complex also que es usado como osmolito para atraer el flujo transpiracional hacia sus propias hojas (Schnabl & Rascke, 1980;Kelly & Horning, 1999). El análisis estadístico indica que U. divaricate acumula mayores cantidades de ciertos minerales que podrían ser usados en el estudio de situaciones especí-ficas, como la fitorremediación (Baxter, 2009).…”
Section: Chlorophyll Content In P Calyculatus and Hostsunclassified
“…Moreover, hemiparasitic plants prefer legumes as hosts because of the greater availability of N (Llugany et al, 2009); this could explain the relatively high protein content of leaf of Psittacanthus. According to the results shown in this study, P. calyculatus is a plant that efficiently extracts nutrients from their hosts, accumulating high levels of K, used as osmolyte to attract transpirational flow to their own leaves (Schnabl & Rascke, 1980;Kelly & Horning, 1999). The statistical analytatistical analysis indicates that U. divaricate accumulates higher amounts of certain minerals that could be used in the study of specific situations, such as phytoremediation (Baxter, 2009).…”
Section: Mineral Content In P Calyculatus and Hostsmentioning
confidence: 99%